2014
DOI: 10.5694/mja14.00106
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccine effectiveness in Australia: results from the Australian Sentinel Practices Research Network

Abstract: Vaccination against influenza was modestly protective, reducing the risk of medical presentation with influenza by around 23%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Eight studies reported the type of swab used, i.e. flocked [31, 67, 100, 91, 94, 95], cellular foam [82] or flocked/cotton [47]. The type of swab and swab site used to collect the sample may affect the quality of the sample collected and therefore sensitivity of the testing procedure [101, 102], although the specificity is likely to be high [103, 104] and so swab quality may only minimally bias VE estimates (see Box 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies reported the type of swab used, i.e. flocked [31, 67, 100, 91, 94, 95], cellular foam [82] or flocked/cotton [47]. The type of swab and swab site used to collect the sample may affect the quality of the sample collected and therefore sensitivity of the testing procedure [101, 102], although the specificity is likely to be high [103, 104] and so swab quality may only minimally bias VE estimates (see Box 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, in one study, the comparison group comprised patients who tested negative for influenza and positive for a non-influenza respiratory virus [67]. In addition, seven studies included sensitivity analyses comparing influenza-positive patients with non-influenza respiratory virus-positive patients as well as pan-negative patients [19, 26, 47, 60, 82, 84, 109]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two other studies from Australia and New Zealand examined vaccine effectiveness estimates for a single influenza season by alternative control groups, and very similar estimates were derived using influenza negative controls and other respiratory viruses positive controls. 29,44 Three other studies that recruited relatively smaller numbers of patients in single influenza seasons found larger differences in vaccine effectiveness point estimates by alternative control groups with overlapping confidence intervals. 21,31,45 Although virus interference was given as a possible explanation for differences in vaccine effectiveness estimates by control group, those studies may have been underpowered to identify real effects.…”
Section: Discussionmentioning
confidence: 99%
“…7,29,41-44 Four studies examined virus interference from pooled estimates over more than one influenza season: one of these studies recruited children in hospitals in Australia, 42 one recruited children from hospitals in Hong Kong, 7 one recruited hospitalized pneumonia patients of all ages in the United States 43 and one included children and older adults seeking ambulatory care or admitted to hospitals in the US. 41 Consistently, no effect of virus interference was detected according to pooled estimates across several influenza seasons in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another network, FluCAN (Australian Influenza Complications Alert Network) [15], records hospital attendance and admissions from patients suffering from influenza across all age groups. These networks allow the estimation of influenza vaccine effectiveness (VE) against medical attendance for community-based individuals [16] and against hospital admission each year [17]. These detection methods are supplemented by a national online weekly reporting surveillance system for cough and fever (Flutracking) [18], as well as a national medical hotline [19], which records enquiries related to ILI.…”
Section: Surveillance In Australia and New Zealandmentioning
confidence: 99%